Method for calculating non-point source pollution distribution in plain rivers - Long-xi Han; Fei Huo; Juan Sun (Water Science and Engineering, 2011)
The land area in a river network is divided into certain-scale square cells for the sake of precision, and, based on the physical mechanisms of rainfall-runoff processes and runoff pollution, the non-point source pollution from cells is estimated using the export coefficients of different land use types. The non-point source pollution from a land cell should all go into the closest river reach, so it is distributed according to the terrain of the plain river network area and the positions of land cells and river network reaches. A relationship between a single land cell and its pollution-receiving reach can be determined using this system. In view of the above, a spatial distribution model of the rainfall runoff and non-point source pollution in reaches of a plain river network area was established. This model can provide technological support for further research on the dynamic effects of non-point source pollution on water quality.